Magnesia adhesive plywood, preparation method thereof and composite structure artificial board

By alternately stacking wooden veneer and magnesium adhesive layers and combining specific materials, magnesium adhesive plywood is prepared, which solves the problems of plywood under the influence of moisture and flame, and realizes high-performance, environmentally friendly plywood products.

CN119874322AActive Publication Date: 2025-04-25FOSHAN GUANGYIKAI MACHINERY CO LTD

Patent Information

Application Number
CN202510380793.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-25
Estimated Expiration
2045-03-28

AI Technical Summary

Technical Problem

Existing plywood is prone to dimensional changes, rot, mold and other problems under the influence of moisture and flame, and traditional aldehyde adhesives have problems such as formaldehyde release, environmental pollution and poor fire resistance.

Method used

Magnesium adhesive is used to replace aldehyde-based adhesive, and magnesium adhesive plywood with alternate stacking of wooden veneers and magnesium adhesive layers, combined with lightly flammed magnesium oxide powder, anhydrous magnesium chloride, water, fly ash, perlite, silane coupling agent, calcium silicate, phosphoric acid, ferric chloride and ethyl orthosilicate and other materials, magnesium adhesive plywood with excellent bonding properties, water resistance and fire resistance are prepared.

Benefits of technology

It achieves good stability, mechanical properties and water resistance of magnesium adhesive plywood, avoids formaldehyde emission and environmental pollution, and improves the fire resistance of the board.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874322A_ABST
    Figure CN119874322A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building board manufacturing, in particular to a magnesium adhesive plywood and a preparation method thereof and a composite structure artificial board, the magnesium adhesive plywood is formed by alternately stacking 2n + 1 layers of wood veneers and 2n layers of magnesium adhesive layers, n is a positive integer, the magnesium adhesive layers are made of magnesium adhesive materials, and the magnesium adhesive layers are made of magnesium adhesive materials. The magnesium adhesive material is prepared from the following raw materials: light calcined magnesia powder, anhydrous magnesium chloride, water, fly ash, perlite, a silane coupling agent, calcium silicate, phosphoric acid, ferric chloride and tetraethoxysilane. According to the magnesium adhesive plywood provided by the invention, excellent bonding capacity is achieved between the wood veneer and the magnesium adhesive layer, so that the magnesium adhesive plywood has good stability and mechanical property, and meanwhile, the magnesium adhesive plywood has excellent water resistance, and is formaldehyde-free and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building board manufacturing, and in particular to a magnesium adhesive plywood and a preparation method thereof and a composite structure artificial board. Background Art

[0002] Plywood is mainly made of fast-growing logs and small-diameter wood, which are peeled into veneers and then processed by gluing, assembly, pressing and other processes. Compared with solid wood, plywood has the advantages of stable structure, good physical and mechanical properties, and small variability. It is widely used in many fields such as furniture manufacturing, construction, packaging, indoor and outdoor decoration, and transportation. The surface wood of plywood is directly exposed to the outside and is easily affected by moisture and flames, resulting in dimensional changes, rotting, mildew and other problems. Even if the fire resistance, wear resistance and flatness are improved through later decorative processing, its service life is still limited and the cost is high due to the loose fit and insufficient adhesion.

[0003] The adhesives used in my country's wood-based panel manufacturing industry are mainly traditional urea-formaldehyde resin, phenol-formaldehyde resin and melamine formaldehyde resin adhesives. Aldehyde adhesives have high strength and fast hardening speed, but they release formaldehyde, polluting the environment and endangering human health. In addition, wood-based panels made with aldehyde adhesives have poor fire resistance and are prone to fire hazards. In recent years, with the increasing demand for wood-based panels in various countries around the world, the defects of aldehyde adhesives and their wood-based panel products have attracted increasing attention.

[0004] To sum up, the development of a flame retardant, fireproof, formaldehyde-free, waterproof and wear-resistant plywood not only meets the current market demand for high-performance and environmentally friendly materials, but is also an important direction to promote the transformation and upgrading of the artificial board industry and achieve sustainable development. Summary of the invention

[0005] The present invention aims to solve one of the technical problems in the prior art to at least a certain extent. To this end, one object of the present invention is to provide a magnesium adhesive plywood and a preparation method thereof and a composite structure artificial board.

[0006] According to a first aspect of the present invention, a magnesium adhesive plywood is provided, wherein the magnesium adhesive plywood is composed of 2n+1 layers of wood veneers and 2n layers of magnesium adhesive layers alternately stacked, where n is a positive integer, wherein the magnesium adhesive layers are formed of a magnesium adhesive material, and the raw materials for preparing the magnesium adhesive material include: light-burned magnesium oxide powder, anhydrous magnesium chloride, water, fly ash, perlite, silane coupling agent, calcium silicate, phosphoric acid, ferric chloride and tetraethyl orthosilicate.

[0007] Specifically, the magnesium adhesive plywood is composed of 3 layers of wood veneers and 2 layers of magnesium adhesive layers stacked alternately. It should be noted that those skilled in the art can select the number of wood veneers and magnesium adhesive layers according to actual needs, for example, the magnesium adhesive plywood has 5 layers of wood veneers and 4 layers of magnesium adhesive layers; another example, the magnesium adhesive plywood has 7 layers of wood veneers and 6 layers of magnesium adhesive layers; another example, the magnesium adhesive plywood has 9 layers of wood veneers and 8 layers of magnesium adhesive layers, etc.

[0008] According to the magnesium adhesive plywood provided by the present invention, magnesium adhesive materials are used to replace aldehyde-based adhesives, and no harmful substances such as formaldehyde are released during use. By using industrial waste fly ash, not only the purpose of environmental protection and cost reduction is achieved, but also fly ash increases the number of micropores in the final material, reduces the thickness of the hydration layer, and forms a denser interpenetrating network structure, which can interact with the silane coupling agent containing a large number of epoxy groups inside, and improve the interface bonding strength between the magnesium adhesive material and the surface of the wooden veneer. The silane coupling agent has a strong chemical reaction activity and has a certain coupling effect. It can react chemically with wood and other components in the magnesium adhesive material at the same time, thereby playing a "bridge" cross-linking role, improving the bonding performance of the magnesium adhesive material, enhancing the mechanical properties of the board, and ensuring that the magnesium adhesive plywood does not delaminate under extremely harsh environments. The main function of perlite is to improve water and fire resistance. Perlite has stable physical and chemical properties, fine voids, high refractoriness, strong water absorption, and superior compressive strength. It is a good inorganic lightweight insulation material. The main function of calcium silicate is to improve the internal bonding strength, elastic modulus, static bending strength and nail holding force of composite structure artificial boards.

[0009] Phosphoric acid can lower the pH value, improve the interfacial bonding between wood and other materials, inhibit the formation of magnesium hydroxide, protect the crystal phase of magnesium cementitious materials, and improve the stability of magnesium adhesives in water; ferric chloride transforms the rod-like 5-phase structure into a more stable gel-like 5-phase structure, and the gel-like structure can fill the micropores of magnesium cementitious materials and wood materials to reduce the infiltration of water; ethyl orthosilicate contains organic and inorganic groups, which can undergo interfacial chemical reactions with wood and magnesium adhesives; ethyl orthosilicate can form a colloid with self-hardening adhesion, form an elastic hydrophobic layer in the adhesive slurry, and coat the magnesium adhesive crystals to a certain extent; and can block the capillary channels between wood and magnesium adhesives, thereby improving water resistance. In the acidic environment provided by phosphoric acid, the iron ions in ferric chloride can form complexes with phosphate ions, guiding the rod-like 5-phase structure to transform into a more stable three-dimensional network-like gel-like 5-phase structure; the phosphate group forms a covalent bond with the hydroxyl group of wood cellulose, realizing chemical bonding between the wood and the adhesive layer and inhibiting the formation of magnesium hydroxide; the silanol group generated by the hydrolysis of ethyl orthosilicate under acidic conditions can undergo a condensation reaction with the hydroxyl group on the wood surface to form a chemical bridge, and realize organic-inorganic hybridization with the iron ion gel network to form a composite colloid, which forms a continuous hydrophobic barrier at the interface between wood and adhesive through the seepage effect, blocking the capillary channel transmission. The water resistance of magnesium adhesive materials can be significantly exerted through the coordinated use of phosphoric acid, ferric chloride and ethyl orthosilicate, thereby improving the overall water resistance of magnesium adhesive plywood.

[0010] Preferably, the raw materials for preparing the magnesium adhesive material include: 55-65 parts by weight of light-burned magnesium oxide powder, 23-25 ​​parts by weight of anhydrous magnesium chloride, 70-80 parts by weight of water, 30-40 parts by weight of fly ash, 2-5 parts by weight of perlite, 1-5 parts by weight of silane coupling agent, 10-20 parts by weight of calcium silicate, 1-3 parts by weight of phosphoric acid, 1-3 parts by weight of ferric chloride and 1-3 parts by weight of tetraethyl orthosilicate.

[0011] More preferably, the raw materials for preparing the magnesium adhesive material include: 60 parts by weight of light-burned magnesium oxide powder, 25 parts by weight of anhydrous magnesium chloride, 75 parts by weight of water, 35 parts by weight of fly ash, 3 parts by weight of perlite, 2 parts by weight of silane coupling agent, 15 parts by weight of calcium silicate, 1 part by weight of phosphoric acid, 1 part by weight of ferric chloride and 1 part by weight of tetraethyl orthosilicate.

[0012] In some embodiments of the present invention, the silane coupling agent is selected from KH560.

[0013] In some embodiments of the present invention, n is a positive integer of 2-7.

[0014] In some embodiments of the present invention, the thickness of a single layer of the magnesium adhesive layer is 0.1 mm-0.3 mm.

[0015] According to the magnesium adhesive plywood provided by the present invention, the preparation method of the magnesium adhesive material comprises: (1) uniformly mixing the anhydrous magnesium chloride, the fly ash, the perlite and the calcium silicate, adding the water and stirring to obtain a brine mixture; (2) adding the light-burned magnesium oxide powder into the brine mixture and mixing them evenly to obtain a mixture; (3) The silane coupling agent, the phosphoric acid, the ferric chloride and the tetraethyl orthosilicate are mixed evenly and then added to the mixture.

[0016] First, anhydrous magnesium chloride, fly ash, perlite and calcium silicate are mixed evenly, and then water is added for stirring. This can avoid the problem of uneven agglomeration and stirring after adding fly ash after adding water to make brine of magnesium chloride and water. The process of adding water will release heat, and the temperature is about 90 degrees. This process should be stirred slowly, and the material is fully dissolved by slow stirring, accelerating the dissolution while minimizing the bubbles and voids in the solution. Then, lightly burned magnesium oxide powder is added to the above brine mixture and mixed evenly, so that the mixture remains in a thick emulsion or cream state, so that it can be mixed evenly with other materials later. Finally, silane coupling agent, phosphoric acid, ferric chloride and ethyl orthosilicate are mixed evenly and added to the mixture to obtain a magnesium adhesive material.

[0017] In some embodiments of the present invention, in step (1), the water is added for no less than 30 min, and the stirring speed does not exceed 20 r / min.

[0018] In some embodiments of the present invention, in step (1), a horizontal mixer is used for stirring, and the mixer is a mixer with a beating bar, which can effectively prevent the material from agglomerating and stir the material evenly.

[0019] In some embodiments of the present invention, in step (2), the time for adding the light-burned magnesium oxide powder to the brine mixture is no more than 30 minutes. The initial setting time after the magnesium oxide and water are mixed is generally within 120 minutes. Completing the mixing within 30 minutes can keep the mixture in a thick emulsion or cream state, which is conducive to more uniform mixing with other materials later.

[0020] In some embodiments of the present invention, in step (3), the silane coupling agent, the phosphoric acid, the ferric chloride and the tetraethyl orthosilicate are mixed evenly and then added to the mixture for no more than 10 minutes. After adding the silane coupling agent, the initial setting time of the magnesium adhesive material will be shortened to about 15 minutes, so it must be mixed quickly and evenly before reaching the initial setting.

[0021] In some embodiments of the present invention, the wooden veneer is immersed in a 2-5wt% sodium hydroxide solution for 2h-4h, then dried to a moisture content of 8-12%, and finally the surface of the dried wooden veneer is roughened using a 15-30 mesh sandpaper. The sodium hydroxide solution can remove the extract and oil components in the wood, release the pores and channels in the wood, and help form the bonding surface of the magnesium adhesive material, avoid and reduce the poor curing of the magnesium adhesive material, and the roughening treatment can increase the roughness of the core board surface, so that the magnesium adhesive material can be better attached to the board surface.

[0022] In a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned magnesium adhesive plywood. The method comprises: Applying the magnesium adhesive material to both sides of the pretreated wood veneer to obtain a glued wood veneer; The wooden veneers and the glued wooden veneers are alternately stacked and then cold pressed at a pressure of 1.0 MPa to 3.5 MPa for 8 hours to 28 hours.

[0023] In some embodiments of the present invention, the pretreatment includes: soaking the wood veneer in a 2-5wt% sodium hydroxide solution for 2h-4h, then drying it to a moisture content of 8-12%, and finally using a 15-30 mesh sand belt to roughen the surface of the dried wood veneer.

[0024] The above-mentioned wood veneers and glued wood veneers are alternately stacked, specifically referring to the distribution in the form of wood veneer-glue wood veneer-wood veneer-glue wood veneer-wood veneer-glue wood veneer-...-wood veneer, and the outermost is the wood veneer. Preferably, the fiber directions of adjacent wood veneers are perpendicular to each other. It should be noted that plywood generally adopts the "odd number layer principle", that is, the number of wood veneers is an odd number.

[0025] The hydration reaction process of the magnesium adhesive material shows that the hot pressing method is not applicable. During hot pressing, the water in the magnesium adhesive material is easily evaporated quickly, which reduces the water involved in the hydration reaction, thereby reducing the strength of the product. Therefore, the present invention adopts the cold pressing method for pressing. Specifically, the cold pressing method includes: cold pressing the wooden veneer and the glued wooden veneer at a pressure of 1.0MPa-3.5MPa for 8h-28h at room temperature.

[0026] In some embodiments of the present invention, the core panel after pressing is naturally cured at room temperature for 7 days.

[0027] At present, there are mainly the following methods to improve the flame retardant properties of plywood. One is to impregnate the veneer with flame retardant or add flame retardant to the adhesive, generally boron flame retardant, nano flame retardant, etc. This method has complex process and high cost. One is to apply flame retardant coating on the surface of plywood. The disadvantage of this method is that it is easy to affect the quality of surface decoration and the flame retardant effect is general. Another method is to coat the surface of plywood with flame retardant materials, such as flame retardant gypsum board, etc. The interface bonding strength between the flame retardant material and the plywood of this method is low, which easily causes the two to separate and cannot meet the application requirements of some heavy-load scenarios.

[0028] In view of this, in a third aspect of the present invention, a composite structure artificial board is proposed, wherein the composite structure artificial board comprises the above-mentioned magnesium adhesive plywood or the magnesium adhesive plywood prepared by the above-mentioned method.

[0029] The composite structure artificial board provided by the present invention comprises a fireproof layer, a fire-resistant layer, the magnesium adhesive plywood, a fire-resistant layer, and a fireproof layer stacked in sequence; The fire-resistant layer is formed by the magnesium adhesive material used to prepare the magnesium adhesive plywood; The fireproof layer is formed by a fireproof slurry, and the raw materials for preparing the fireproof slurry include: 55-65 parts by weight of light-burned magnesium oxide powder, 20-25 parts by weight of anhydrous magnesium chloride, 6-8 parts by weight of magnesium sulfate heptahydrate, 55-65 parts by weight of water, 30-40 parts by weight of fly ash, 8-12 parts by weight of polypropylene fiber, 5-8 parts by weight of red mud, and 6-10 parts by weight of aluminum tripolyphosphate.

[0030] According to the above-mentioned composite structure artificial board provided by the present invention, a magnesium adhesive material is used to form a fireproof layer, and the above-mentioned fireproof slurry is selected to form a fireproof layer. First, the magnesium adhesive material has excellent bonding properties, which can be well combined with the wooden layers (i.e., wooden veneers) on both sides of the magnesium adhesive plywood. Secondly, the fireproof slurry selected by the present invention not only has excellent fireproof and mechanical properties, but also has good bonding properties with the fireproof layer. A stable bonding interface can be formed between the fireproof layer and the fireproof layer, thereby ensuring the stability of the entire composite structure artificial board, and it will not delaminate even in extreme environments. Compared with adding adhesives as a whole to the fireproof layer, the present invention uses a fireproof layer as a connecting layer between the magnesium adhesive plywood and the fireproof layer, which not only significantly reduces the production cost, but also ensures the excellent stability of the composite structure artificial board.

[0031] The fireproof slurry used in the present invention has excellent fireproof performance and mechanical properties. Fly ash can increase elasticity and improve the mechanical properties of the final product. Magnesium sulfate heptahydrate can inhibit the phenomenon of "return of salt and bloom". Polypropylene fiber can improve the impact resistance of the fireproof layer, aluminum tripolyphosphate can inhibit the corrosion of the fireproof layer by the external environment, and significantly improve the fire resistance; the role of adding red mud is mainly to improve the water resistance; polypropylene fiber, aluminum tripolyphosphate and red mud play a synergistic role in improving the performance of the fireproof layer, which can enhance the impact resistance, compression resistance, fireproof performance and water resistance.

[0032] Specifically, magnesium oxide and magnesium chloride are mixed in a certain proportion, and magnesium sulfate heptahydrate, ferric chloride, ethyl orthosilicate, etc. are added at the same time, so as to reasonably control the Cl ion content and the generation of free Cl ions to reduce moisture absorption and halogen return. In addition, by adding fly ash, red mud, polypropylene fiber, etc., the fireproof slurry is toughened and modified, so that the surface wear resistance and water resistance of the finished product are greatly improved. At the same time, the inorganic components can effectively isolate oxygen at high temperatures to prevent the spread of combustion.

[0033] In some embodiments of the present invention, the thickness of the magnesium adhesive plywood is 9 mm-25 mm.

[0034] In some embodiments of the present invention, the thickness of a single layer of the fire-resistant layer is 1 mm-7 mm.

[0035] In some embodiments of the present invention, the thickness of a single layer of the fireproof layer is 3 mm-25 mm.

[0036] In some embodiments of the present invention, the preparation method of the fireproof slurry is as follows: (a) the anhydrous magnesium chloride, the fly ash and the magnesium sulfate heptahydrate are mixed evenly, and then the water is added and stirred to obtain a brine material; (b) the light-burned magnesium oxide powder is added to the brine material and mixed evenly to obtain an intermediate material; (c) the polypropylene fiber, the red mud and the aluminum tripolyphosphate are mixed evenly, and then the intermediate material is added.

[0037] In some embodiments of the present invention, in step (a), the water is added for no less than 30 min, and the stirring speed does not exceed 20 r / min.

[0038] In some embodiments of the present invention, in step (a), a horizontal mixer is used for stirring, and the mixer is a mixer with a beating bar, which can effectively prevent the material from agglomerating and stir evenly.

[0039] In some embodiments of the present invention, in step (b), the time for adding the light-burned magnesium oxide powder to the brine material is no more than 30 minutes. The initial setting time after the magnesium oxide and water are mixed is generally within 120 minutes. If the mixing is completed within 30 minutes, the mixture can be kept in a thick emulsion or cream state, which is conducive to more uniform mixing with other materials later.

[0040] In some embodiments of the present invention, the method for preparing the composite structure artificial board comprises: (1) Magnesium adhesive material is laid on the bottom layer of the mold, magnesium adhesive plywood is placed on the upper layer of the magnesium adhesive material, and magnesium adhesive material is laid again on the upper layer of the magnesium adhesive plywood, so that the thickness of magnesium adhesive material on both sides of the magnesium adhesive plywood is consistent, and then cold pressing is performed at room temperature for 6h-10h at a pressure of 1.2MPa-1.6MPa to obtain a slab; (2) drying, edge sawing, leveling and sanding the slab, and roughening it with a 15-30 mesh sanding belt; (3) Spread fireproof slurry on the bottom layer of the mold, place the slab processed in step 2 on the top layer of the fireproof slurry, and then spread fireproof slurry again on the top layer of the slab to make the thickness of the fireproof slurry on both sides of the slab consistent, and then cold press at room temperature at a pressure of 1.0MPa-2MPa for 8h-48h; (4) drying, edge sawing, leveling and sanding the slab obtained in step (3), and naturally curing it at room temperature for 14 days. During the curing period, the surface needs to be sprayed with water to keep it moist; (5) subjecting the slab cured in step (4) to a second cold pressing, wherein the second cold pressing has a unit pressure of 1.0 MPa to 2.0 MPa, a pressing time of 1 h to 3 h, and a temperature of room temperature; (6) Drying, baking, sawing and sanding the slab after the second cold pressing to obtain a composite structure artificial board.

[0041] The roughening treatment can increase the contact area between the refractory layer and the fireproof layer and enhance the interfacial bonding strength. The reason for keeping the surface moist is that the hydration process is a continuous process, and is accompanied by slow heat release. When the water evaporates, the whiskers of the 518 crystals formed will be destroyed, and the structure of the whiskers of the 518 crystals is the key to forming an interpenetrating network structure. Therefore, keeping the surface moist will slow down the evaporation rate of water, and at the same time make the material fully hydrated, which is conducive to the process of hydration reaction. The reason for curing for 14 days is that, generally speaking, the longer the curing time, the more sufficient the hydration reaction, the more crystalline content, and the stronger the mechanical properties of the manufactured board. On the basis of the fireproof slurry of the present invention, the time cost and the quality of the board obtained at different curing times are comprehensively considered, and the optimal curing time is 14 days. The role of the secondary cold pressing is mainly to further improve the density and strength of the board, enhance the internal bonding strength of the board, and improve the stability and durability of the board.

[0042] The present invention has at least the following technical effects: (1) The magnesium adhesive plywood provided by the present invention has excellent bonding ability between the wood veneer and the magnesium adhesive layer, thereby ensuring that the magnesium adhesive plywood has good stability and mechanical properties. At the same time, the magnesium adhesive plywood has excellent water resistance and is formaldehyde-free and environmentally friendly.

[0043] (2) The composite structure artificial board provided by the present invention has excellent stability, fire resistance and mechanical properties, and the composite structure artificial board is environmentally friendly and safe, with low production cost. The board can maintain stable fire resistance and water resistance during long-term use. Its physical properties and water resistance can exceed the level of traditional boards, and can meet the market demand for high-performance, environmentally friendly materials.

[0044] (3) The composite structure artificial board provided by the present invention adopts a five-layer composite structure design that is symmetrical up and down, with a simple process and low cost. The main materials of the fireproof layer and the fire-resistant layer on both sides and the adhesive used in the magnesium adhesive plywood are all inorganic magnesium cementitious materials, and no aldehyde-based adhesive is used. The magnesium adhesive plywood and the composite structure artificial board can be produced by a cold pressing process, which does not produce toxic and harmful substances, no free formaldehyde, saves energy, and is green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0046] Figure 1 This is a structural example diagram of the magnesium adhesive plywood provided by the present invention; Figure 2 It is a partial structural schematic diagram of a horizontal mixer used in the preparation of magnesium adhesive material in the present invention; Figure 3 It is a schematic diagram of the preparation process of the magnesium adhesive material provided by the present invention; Figure 4 This is a structural example diagram of the composite structure artificial board provided by the present invention; Figure 5 It is a schematic diagram of the preparation process of the fireproof slurry provided by the present invention; Figure 6 The present invention provides a process flow chart for preparing the composite structure artificial board. DETAILED DESCRIPTION

[0047] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0048] Example 1 This embodiment provides a magnesium adhesive plywood, the structure of which can be referred to Figure 1 The magnesium adhesive plywood is composed of multiple layers of wood veneers 1 and multiple layers of magnesium adhesive layers 2 stacked alternately. Specifically, the magnesium adhesive plywood has 13 layers of wood veneers 1 and 12 layers of magnesium adhesive layers 2, and the thickness of a single magnesium adhesive layer is 0.2 mm.

[0049] (1) The raw materials for the preparation of magnesium adhesive materials are as follows: 60 parts by weight of light-burned magnesium oxide powder, 25 parts by weight of anhydrous magnesium chloride, 75 parts by weight of water, 35 parts by weight of fly ash, 3 parts by weight of perlite, 2 parts by weight of silane coupling agent (KH560), 15 parts by weight of calcium silicate, 1 part by weight of phosphoric acid, 1 part by weight of ferric chloride and 1 part by weight of tetraethyl orthosilicate.

[0050] (2) The preparation process of magnesium adhesive material is as follows: Step 1. Mix anhydrous magnesium chloride, fly ash, perlite and calcium silicate in a horizontal mixer with a stirrer and remove them for use; Figure 2 The horizontal mixer includes a mixing chamber 200 and a beating rod 300 located in the mixing chamber 200. The present invention adds the mixed material 100 into the mixing chamber 200 and rotates the mixing chamber 200 so that the mixed material 100 therein is evenly mixed under the action of the beating rod 300.

[0051] Step 2. Add water in batches to the mixture obtained in step 1. Heat will be released during this process, and the temperature is about 90 degrees. Stir slowly during this process, and the speed of the planetary mixer shall not exceed 20r / min. This process needs to be controlled for more than 30 minutes; Step 3. gradually add the light-burned magnesium oxide to the brine mixture obtained in step 2 and mix well. This process should be completed within 30 minutes; Step 4. Evenly mix KH560 silane coupling agent, phosphoric acid, ferric chloride and tetraethyl orthosilicate to obtain a composite modifier, and then add it to the mixture obtained in step 3 in batches. This process must be completed within 10 minutes to obtain a magnesium adhesive material.

[0052] (3) The preparation process of magnesium adhesive plywood is as follows: Step 1. Peel the logs into 1.0 mm-3.0 mm wood veneers, soak the wood veneers in a 3 wt % sodium hydroxide solution for 3 h, and then dry them to a moisture content of 8-12%, and finally use a 20-mesh sanding belt to roughen the surface of the dried wood veneer.

[0053] Step 2. Apply the magnesium adhesive material to both sides of the roughened wood veneer to obtain a glued wood veneer. Stack the wood veneer, glued wood veneer, wood veneer, ..., glued wood veneer, and wood veneer, and then cold press them at room temperature under a pressure of 2 MPa for 15 hours.

[0054] Step 3. The magnesium adhesive plywood after pressing is naturally cured at room temperature for 7 days.

[0055] This embodiment provides a composite structure artificial board, and its specific structure is as follows Figure 4 As shown, it includes a fireproof layer 10, a fire-resistant layer 20, the magnesium adhesive plywood 30, a fire-resistant layer 20, and a fireproof layer 10 stacked in sequence, the thickness of the magnesium adhesive plywood is 18 mm, the thickness of the single-layer fire-resistant layer is 2 mm, and the thickness of the single-layer fireproof layer is 9 mm.

[0056] (1) The refractory layer adopts the magnesium adhesive material provided in this embodiment.

[0057] (2) The raw materials for preparing the fireproof slurry used in the fireproof layer are as follows: 60 parts by weight of light-burned magnesium oxide powder, 22 parts by weight of anhydrous magnesium chloride, 7 parts by weight of magnesium sulfate heptahydrate, 60 parts by weight of water, 35 parts by weight of fly ash, 10 parts by weight of polypropylene fiber, 6 parts by weight of red mud, and 8 parts by weight of aluminum tripolyphosphate.

[0058] (3) The preparation process of fireproof slurry is as follows: Step a. Mix anhydrous magnesium chloride, fly ash and magnesium sulfate heptahydrate and remove them for use; Step b. Add water in batches to the mixture obtained in step a. Heat will be released during this process, and the temperature is about 90 degrees. Stir slowly during this process, and the speed of the planetary mixer shall not exceed 20r / min. This process needs to be controlled for more than 30 minutes; Step c. gradually add the lightly burned magnesium oxide powder to the brine mixture obtained in step b and mix well. This process must be completed within 30 minutes; Step d. Mix the polypropylene fiber, red mud and aluminum tripolyphosphate evenly, then add them to the mixture obtained in step 3 in batches and mix evenly to obtain a fireproof slurry.

[0059] (4) The preparation process of composite structure artificial board is as follows: Step ①. Pave the bottom layer of the mold with a magnesium adhesive material, place the magnesium adhesive plywood prepared in this embodiment on the upper layer of the magnesium adhesive material, and then pave the magnesium adhesive material again on the upper layer of the magnesium adhesive plywood to make the magnesium adhesive material on both sides of the magnesium adhesive plywood have the same thickness, and then cold press at room temperature for 8h at a pressure of 1.4MPa to obtain a slab; Step ②. The slab is dried, sawed, leveled and sanded, and roughened using a 20-mesh sanding belt; Step ③. The fireproof slurry prepared above is paved on the bottom of the mold, and the slab treated in step ② is placed on the upper layer of the fireproof slurry, and then the fireproof slurry is paved again on the upper layer of the slab to make the thickness of the fireproof slurry on both sides of the slab consistent, and then cold pressed at room temperature for 25h at a pressure of 1.5MPa; Step ④. The slab obtained in step ③ is dried, sawed, leveled and sanded, and naturally cured at room temperature for 14 days. During the curing period, the surface needs to be sprayed with water to keep the surface moist; Step ⑤. The slab cured in step ④ is subjected to secondary cold pressing at room temperature, with a unit pressure of 1.5 MPa and a pressing time of 2 h; Step ⑥: Dry, bake, saw edge and sand the slab after the secondary cold pressing to obtain a composite structure artificial board.

[0060] Example 2 This embodiment provides a magnesium adhesive plywood, and the difference between Embodiment 2 and Embodiment 1 is as follows: (1) The raw materials for the preparation of magnesium adhesive materials are as follows: 60 parts by weight of light-burned magnesium oxide powder, 25 parts by weight of anhydrous magnesium chloride, 75 parts by weight of water, 35 parts by weight of fly ash, 3 parts by weight of perlite, 2 parts by weight of silane coupling agent (KH560), 15 parts by weight of calcium silicate, 2 parts by weight of phosphoric acid, 2 parts by weight of ferric chloride and 2 parts by weight of ethyl orthosilicate.

[0061] Comparative Example 1 This comparative example provides a magnesium adhesive plywood, and the difference between comparative example 1 and example 1 is as follows: (1) The raw materials for the preparation of magnesium adhesive materials are as follows: 60 parts by weight of light-burned magnesium oxide powder, 25 parts by weight of anhydrous magnesium chloride, 75 parts by weight of water, 35 parts by weight of fly ash, 3 parts by weight of perlite, 2 parts by weight of silane coupling agent (KH560) and 15 parts by weight of calcium silicate.

[0062] This comparative example provides a composite structure artificial board, and the difference between comparative example 1 and embodiment 1 is: The fire-resistant layer used in the composite structure artificial board of Comparative Example 1 is the magnesium adhesive material prepared in Comparative Example 1, and the magnesium adhesive plywood uses the magnesium adhesive plywood prepared in Comparative Example 1.

[0063] Comparative Example 2 This comparative example provides a magnesium adhesive plywood, and the difference between comparative example 2 and example 1 is as follows: (1) The raw materials for the preparation of magnesium adhesive materials are as follows: 60 parts by weight of light-burned magnesium oxide powder, 25 parts by weight of anhydrous magnesium chloride, 75 parts by weight of water, 35 parts by weight of fly ash, 3 parts by weight of perlite, 2 parts by weight of silane coupling agent (KH560), 15 parts by weight of calcium silicate and 3 parts by weight of phosphoric acid.

[0064] Comparative Example 3 This comparative example provides a magnesium adhesive plywood, and the difference between comparative example 3 and example 1 is as follows: (1) The raw materials for the preparation of magnesium adhesive materials are as follows: 60 parts by weight of light-burned magnesium oxide powder, 25 parts by weight of anhydrous magnesium chloride, 75 parts by weight of water, 35 parts by weight of fly ash, 3 parts by weight of perlite, 2 parts by weight of silane coupling agent (KH560), 15 parts by weight of calcium silicate and 3 parts by weight of ferric chloride.

[0065] Comparative Example 4 This comparative example provides a magnesium adhesive plywood, and the difference between comparative example 4 and example 1 is as follows: (1) The raw materials for the preparation of magnesium adhesive materials are as follows: 60 parts by weight of light-burned magnesium oxide powder, 25 parts by weight of anhydrous magnesium chloride, 75 parts by weight of water, 35 parts by weight of fly ash, 3 parts by weight of perlite, 2 parts by weight of silane coupling agent (KH560), 15 parts by weight of calcium silicate and 3 parts by weight of ethyl orthosilicate.

[0066] Comparative Example 5 This comparative example provides a magnesium adhesive plywood, and the difference between comparative example 5 and example 1 is as follows: (1) The raw materials for the preparation of magnesium adhesive materials are as follows: 60 parts by weight of light-burned magnesium oxide powder, 25 parts by weight of anhydrous magnesium chloride, 75 parts by weight of water, 35 parts by weight of fly ash, 3 parts by weight of perlite, 2 parts by weight of silane coupling agent (KH560), 15 parts by weight of calcium silicate, 1 part by weight of phosphoric acid and 2 parts by weight of ferric chloride.

[0067] Comparative Example 6 This comparative example provides a magnesium adhesive plywood, and the difference between comparative example 6 and example 1 is as follows: (1) The raw materials for the preparation of magnesium adhesive materials are as follows: 60 parts by weight of light-burned magnesium oxide powder, 25 parts by weight of anhydrous magnesium chloride, 75 parts by weight of water, 35 parts by weight of fly ash, 3 parts by weight of perlite, 2 parts by weight of silane coupling agent (KH560), 15 parts by weight of calcium silicate, 2 parts by weight of phosphoric acid and 1 part by weight of ethyl orthosilicate.

[0068] Comparative Example 7 This comparative example provides a magnesium adhesive plywood, and the difference between comparative example 7 and example 1 is as follows: (1) The raw materials for the preparation of magnesium adhesive materials are as follows: 60 parts by weight of light-burned magnesium oxide powder, 25 parts by weight of anhydrous magnesium chloride, 75 parts by weight of water, 35 parts by weight of fly ash, 3 parts by weight of perlite, 2 parts by weight of silane coupling agent (KH560), 15 parts by weight of calcium silicate, 1 part by weight of ferric chloride and 2 parts by weight of ethyl orthosilicate.

[0069] Comparative Example 8 This comparative example provides a magnesium adhesive plywood, and its preparation raw materials and preparation process are the same as those in Example 1.

[0070] This comparative example provides a composite structure artificial board. The difference between comparative example 8 and embodiment 1 is as follows: (2) The raw materials for preparing the fireproof slurry used in the fireproof layer are as follows: 60 parts by weight of light-burned magnesium oxide powder, 22 parts by weight of anhydrous magnesium chloride, 7 parts by weight of magnesium sulfate heptahydrate, 60 parts by weight of water, 35 parts by weight of fly ash, and 10 parts by weight of polypropylene fiber.

[0071] Comparative Example 9 This comparative example provides a magnesium adhesive plywood, and its preparation raw materials and preparation process are the same as those in Example 1.

[0072] This comparative example provides a composite structure artificial board, and the difference between comparative example 9 and embodiment 1 is: (2) The raw materials for preparing the fireproof slurry used in the fireproof layer are as follows: 60 parts by weight of light-burned magnesium oxide powder, 22 parts by weight of anhydrous magnesium chloride, 7 parts by weight of magnesium sulfate heptahydrate, 60 parts by weight of water, 35 parts by weight of fly ash, 10 parts by weight of polypropylene fiber, and 14 parts by weight of red mud.

[0073] Comparative Example 10 This comparative example provides a magnesium adhesive plywood, and its preparation raw materials and preparation process are the same as those in Example 1.

[0074] This comparative example provides a composite structure artificial board, and the difference between comparative example 10 and embodiment 1 is: (2) The raw materials for preparing the fireproof slurry used in the fireproof layer are as follows: 60 parts by weight of light-burned magnesium oxide powder, 22 parts by weight of anhydrous magnesium chloride, 7 parts by weight of magnesium sulfate heptahydrate, 60 parts by weight of water, 35 parts by weight of fly ash, 10 parts by weight of polypropylene fiber, and 14 parts by weight of aluminum tripolyphosphate.

[0075] Comparative Example 11 This comparative example provides a magnesium adhesive plywood, and its preparation raw materials and preparation process are the same as those in Example 1.

[0076] The comparative example provides a composite structure artificial board, and the difference between the comparative example 11 and the embodiment 1 is: The composite structure artificial board of comparative example 11 has no fire-resistant layer but only a fireproof layer, that is, the fireproof layer is prepared on both sides of the magnesium adhesive plywood. The raw materials and preparation process of the specific fireproof layer are the same as those in Example 1.

[0077] Comparative Example 12 This comparative example provides a magnesium adhesive plywood, and its preparation raw materials and preparation process are the same as those in Example 1.

[0078] The comparative example provides a composite structure artificial board, and the difference between comparative example 12 and embodiment 1 is: The composite structure artificial board of Comparative Example 12 has only a fire-resistant layer.

[0079] Comparative Example 13 This comparative example provides a magnesium adhesive plywood, and the difference between comparative example 13 and example 1 is: The wooden veneer used in Comparative Example 13 was not roughened.

[0080] The comparative example provides a composite structure artificial board, and the difference between comparative example 13 and embodiment 1 is that: (4) the slab in step ② in the preparation process of the composite structure artificial board is not roughened.

[0081] Comparative Example 14 This comparative example provides a magnesium adhesive plywood, and the difference between comparative example 14 and example 1 is: The wood veneer used in Comparative Example 14 was roughened with a 40-mesh sanding belt.

[0082] The comparative example provides a composite structure artificial board, and the difference between comparative example 14 and embodiment 1 is that: (4) the slab in step ② in the preparation process of the composite structure artificial board is roughened by a 40-mesh sand belt.

[0083] Comparative Example 15 This comparative example provides a magnesium adhesive plywood, and the difference between comparative example 15 and example 1 is: The wood veneer used in Comparative Example 15 was roughened with a 60-mesh sanding belt.

[0084] The comparative example provides a composite structure artificial board, and the difference between comparative example 15 and embodiment 1 is that: (4) the slab in step ② in the preparation process of the composite structure artificial board is roughened by a 60-mesh sand belt.

[0085] In order to verify the performance of the magnesium adhesive plywood and composite structure artificial board of the present invention, tests were performed on them, as follows: (1) The water resistance of the magnesium adhesive plywood provided in Examples 1-2 and Comparative Examples 1-7 was tested.

[0086] Dip stripping length: Method: 4.19 of GB / T 17657-2022, Test Methods for Physical and Chemical Properties of Artificial Boards and Faced Artificial Boards. The specimen is immersed in boiling water for 4 hours, taken out and placed in a drying oven at (63±3)℃ for 20 hours, and then immersed in boiling water for 4 hours, taken out and placed in a drying oven at (63±3)℃ for 3 hours. Carefully observe whether there is peeling and delamination between the adhesive layers of the specimen or between the veneer layer and the substrate. Use a steel ruler to measure the length of the peeling or delamination of each side of each adhesive layer of the specimen.

[0087] Standard: "Ordinary Plywood" GB / T9846-2015 requires that the cumulative peeling length of each side of the same adhesive layer of each specimen shall not exceed 25mm.

[0088] 24h water absorption: Method: According to 4.9 of GB / T 17657-2022, Test Methods for Physical and Chemical Properties of Wood-Based Panels and Faced Wood-Based Panels, after the specimen is immersed in water for 24 h±15 min, take out the specimen, wipe off the surface moisture with a wet cloth, weigh it within 10 min, and calculate the ratio of the mass difference before and after 24 h immersion to the mass before immersion.

[0089] The water resistance test results of the magnesium adhesive plywood provided in Examples 1-2 and Comparative Examples 1-7 are shown in Table 1.

[0090] Table 1

[0091] It can be seen from Table 1 that adding phosphoric acid, ferric chloride and ethyl orthosilicate to the magnesium adhesive material can significantly improve the water resistance of the magnesium adhesive plywood.

[0092] (2) The boiling water resistance of the magnesium adhesive plywood and the composite structure artificial board provided in Example 1 and Comparative Example 1 was tested.

[0093] Composite structure artificial boards can be used for building decoration materials. The sides of the boards are generally not sealed, and their working environment may be a humid environment. Therefore, it is necessary to consider the impact of the water resistance of the core of the composite structure artificial board on the overall water resistance of the composite board, so a boiling water resistance test is carried out. The details of the boiling water resistance test are as follows: Method: According to 4.52 of GB / T 17657-2022, Test methods for physical and chemical properties of wood-based panels and veneer wood-based panels, the increase in mass and thickness of each specimen after immersion in boiling water for 2 h, as well as the presence or absence of appearance changes such as bubbling or delamination, are determined.

[0094] Surface quality rating is based on the surface quality and edge quality of the test piece.

[0095] Surface quality rating: Level 5: No change; Level 4: Slight change in gloss and / or color at a certain angle; Level 3: Moderate change in gloss and / or color; Level 2: Obvious change in gloss and / or color; Level 1: Bubbling and / or delamination.

[0096] Edge Quality Rating: Level 5: No obvious changes; Level 4: Slight edge cracks visible to the naked eye; Level 3: Moderate edge cracks; Level 2: Severe edge cracks; Level 1: Core layer delamination.

[0097] The boiling water resistance test results of the magnesium adhesive plywood and composite structure artificial board provided in Example 1 and Comparative Example 1 are shown in Table 2.

[0098] Table 2

[0099] It can be seen from Table 2 that the magnesium adhesive plywood and the composite structure artificial board of the present invention both have a certain boiling water resistance.

[0100] (3) The fireproof slurries of Example 1 and Comparative Examples 8-10 were pressed into plates and their water resistance and mechanical properties were tested. The specific process of pressing plate is as follows: Step 1. Mechanically spread the fireproof slurry evenly into the mold, and control its paving thickness to be about 10mm; Step 2. The mold is placed in a press and cold pressed at room temperature for 12 hours at a pressure of 1.5 MPa; Step 3. The slab is dried, sawed, leveled and sanded, and naturally cured at room temperature for 14 days. During the curing period, the surface needs to be sprayed with water to keep it moist; Step 4. The cured slab is subjected to secondary cold pressing at room temperature, with a unit pressure of 1.5 MPa and a pressing time of 2 h; Step 5. Dry, bake, saw edge and sand the slab after the secondary cold pressing.

[0101] Softening coefficient (water resistance): Softening coefficient α is the compressive strength R of the fireproof layer after 28 days of air curing. α The compressive strength R of the fireproof layer after 28 days of air curing and 28 days of water immersion w The ratio of α = R w / R α .

[0102] Static flexural strength and elastic modulus (mechanical properties): Test methods for physical and chemical properties of wood-based panels and veneer wood-based panels, 4.7 in GB / T17657-2022, static flexural strength is the ratio of the bending moment and the bending section modulus of the specimen under the maximum load; the elastic modulus is the ratio of the stress and strain generated by the load when the specimen is within the elastic limit of the material.

[0103] The static bending strength and elastic modulus of three-point bending are measured by applying a load to the middle of the specimen supported at two points. The maximum load is recorded.

[0104] The test results of mechanical properties and water resistance of the fireproof slurry after pressing plate of Example 1 and Comparative Examples 8-10 are shown in Table 3.

[0105] Table 3

[0106] As can be seen from Table 3, adding red mud to the fireproof slurry can significantly enhance the water resistance, and adding aluminum tripolyphosphate can significantly enhance the mechanical properties. After balancing the addition amounts of the two, the composite structure artificial board of the present invention can have excellent water resistance and mechanical properties at the same time.

[0107] (4) The impact resistance, abrasion resistance and flame retardancy of the magnesium adhesive plywood and the composite structure wood-based panel of Example 1 and the composite structure wood-based panels of Comparative Examples 11-12 were tested.

[0108] Bonding strength: refers to the ability of the glue layer to resist tensile failure, usually expressed as the maximum tensile force per unit area. According to GB / T 17657-2022, the bonding strength test is to use a tensile load to cause shear failure in the glue layer of the specimen, thereby determining the bonding quality of the composite structure artificial board.

[0109] Impact deformation: "Test methods for wood structures. Soft impact test on wood frame walls" EN 596:1995, a heavy object is impacted on the specimen panel under human action, and the maximum residual deformation is recorded.

[0110] Abrasion value: 4.47 in "Test Methods for Physical and Chemical Properties of Wood-Based Panels and Faced Wood-Based Panels" GB / T 17657-2022, which refers to the amount of surface wear after a certain number of relative friction between the product surface and a pair of grinding wheels with emery cloth.

[0111] Flame retardant time: "Test method for flammability of building materials" GB / T 8626-2007, use a small flame to directly impact the vertically placed test piece and record the time it takes for the dripping material to ignite the filter paper.

[0112] Table 4

[0113] As can be seen from Table 4, the composite structure artificial board of the present invention has excellent flame retardant properties, and the fireproof layer and the fireproof layer have strong bonding force. The composite structure artificial board has excellent stability, wear resistance and impact resistance. (5) The bonding strength between the wood veneer and the magnesium adhesive layer, the magnesium adhesive plywood and the fire-resistant layer, and the fire-resistant layer and the fireproof layer of the magnesium adhesive plywood of Example 1 and Comparative Examples 13-15.

[0114] See Table 5 for specific results.

[0115] Table 5

[0116] It can be seen from Table 5 that by roughening the wood veneer and the fire-resistant layer to a certain extent, the bonding strength between the layers can be significantly improved.

[0117] (6) The mechanical properties of the composite structure artificial board prepared in Example 1 were tested. The specific results are shown in Table 6.

[0118] Table 6

[0119] The fire rating of the composite structure artificial board prepared in Example 1 was tested, and the specific results are shown in Table 7.

[0120]

[0121] The fire protection grade meets B1 requirements.

[0122] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A magnesium adhesive plywood, characterized in that: The invention is composed of 2n+1 layers of wood veneer and 2n layers of magnesium adhesive layers alternately stacked, where n is a positive integer, wherein the magnesium adhesive layer is formed of a magnesium adhesive material, and the raw materials for preparing the magnesium adhesive material include: light-burned magnesium oxide powder, anhydrous magnesium chloride, water, fly ash, perlite, silane coupling agent, calcium silicate, phosphoric acid, ferric chloride and tetraethyl orthosilicate.

2. The magnesium adhesive plywood according to claim 1, characterized in that: The raw materials for preparing the magnesium adhesive material include: 55-65 parts by weight of light-burned magnesium oxide powder, 23-25 ​​parts by weight of anhydrous magnesium chloride, 70-80 parts by weight of water, 30-40 parts by weight of fly ash, 2-5 parts by weight of perlite, 1-5 parts by weight of silane coupling agent, 10-20 parts by weight of calcium silicate, 1-3 parts by weight of phosphoric acid, 1-3 parts by weight of ferric chloride and 1-3 parts by weight of tetraethyl orthosilicate; and / or, n is a positive integer from 2 to 7; And / or, the thickness of the single layer of magnesium adhesive layer is 0.1 mm-0.3 mm.

3. The magnesium adhesive plywood according to claim 1 or 2, characterized in that: The preparation method of the magnesium adhesive material comprises: (1) uniformly mixing the anhydrous magnesium chloride, the fly ash, the perlite and the calcium silicate, adding the water and stirring to obtain a brine mixture; (2) adding the light-burned magnesium oxide powder into the brine mixture and mixing them evenly to obtain a mixture; (3) The silane coupling agent, the phosphoric acid, the ferric chloride and the tetraethyl orthosilicate are mixed evenly and then added to the mixture.

4. The magnesium adhesive plywood according to claim 3, characterized in that: In step (1), the water is added for no less than 30 minutes, and the stirring speed does not exceed 20 r / min; And / or, in step (2), the time for adding the light-burned magnesium oxide powder to the brine mixture is no more than 30 minutes; And / or, in step (3), the silane coupling agent, the phosphoric acid, the ferric chloride and the tetraethyl orthosilicate are mixed evenly and then added to the mixture for no more than 10 minutes.

5. A method for preparing magnesium adhesive plywood according to any one of claims 1 to 4, characterized in that: include: Applying magnesium adhesive material to both sides of the pretreated wood veneer to obtain a glued wood veneer; The wooden veneers and the glued wooden veneers are alternately stacked and then cold pressed at a pressure of 1.0 MPa to 3.5 MPa for 8 hours to 28 hours.

6. The method for preparing magnesium adhesive plywood according to claim 5, characterized in that: The pretreatment includes: soaking the wooden veneer in a 2-5wt% sodium hydroxide solution for 2h-4h, drying it to a moisture content of 8-12%, and finally roughening the surface of the dried wooden veneer using a 15-30 mesh sanding belt.

7. A composite structure artificial board, characterized in that: It comprises the magnesium adhesive plywood described in any one of claims 1 to 4 or the magnesium adhesive plywood prepared according to the preparation method described in any one of claims 5 to 6.

8. The composite structure artificial board according to claim 7, characterized in that: It includes a fireproof layer, a fire-resistant layer, the magnesium adhesive plywood, a fire-resistant layer, and a fireproof layer stacked in sequence; The fire-resistant layer is formed by the magnesium adhesive material used to prepare the magnesium adhesive plywood; The fireproof layer is formed by a fireproof slurry, and the raw materials for preparing the fireproof slurry include: 55-65 parts by weight of light-burned magnesium oxide powder, 20-25 parts by weight of anhydrous magnesium chloride, 6-8 parts by weight of magnesium sulfate heptahydrate, 55-65 parts by weight of water, 30-40 parts by weight of fly ash, 8-12 parts by weight of polypropylene fiber, 5-8 parts by weight of red mud, and 6-10 parts by weight of aluminum tripolyphosphate.

9. The composite structure artificial board according to claim 8, characterized in that: The thickness of the magnesium adhesive plywood is 9mm-25mm; And / or, the thickness of the single-layer refractory layer is 1 mm to 7 mm; And / or, the thickness of the single-layer fireproof layer is 3mm-25mm.

10. The composite structure artificial board according to claim 8 or 9, characterized in that: The preparation method of the fireproof slurry is as follows: The anhydrous magnesium chloride, the fly ash and the magnesium sulfate heptahydrate are uniformly mixed, and then the water is added and stirred to obtain a brine material; Adding the light-burned magnesium oxide powder into the brine material and mixing evenly to obtain an intermediate material; The polypropylene fiber, the red mud and the aluminum tripolyphosphate are uniformly mixed and then added into the intermediate material.

Citation Information

Patent Citations

  • Multilayer flame-retardant wood-based composite board and manufacturing method thereof

    CN106003908A

  • Inorganic plywood and production method thereof

    CN108237602A

  • Composite plate formed by bonding mixed cement materials on the outer side of organic warming plate

    CN202466864U

Cited By

  • Inorganic composite environment-friendly flame-retardant plate and preparation method thereof

    CN120840171A